1998
DOI: 10.1161/01.res.82.12.1263
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in the Control of Renal Oxygen Consumption and the Regulation of Chemical Work in the Kidney

Abstract: Inhibition of NO synthesis has recently been shown to increase oxygen extraction in vivo, and NO has been proposed to play a significant role in the regulation of oxygen consumption by both skeletal and cardiac muscle in vivo and in vitro. It was our aim to determine whether NO also has such a role in the kidney, a tissue with a relatively low basal oxygen extraction. In chronically instrumented conscious dogs, administration of an inhibitor of NO synthase, nitro-L-arginine (NLA, 30 mg/kg i.v.), caused a maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
90
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 31 publications
10
90
0
2
Order By: Relevance
“…; and (3) Can the vascular and/or tubular architecture influence the observations? All NOS isoforms are expressed in the kidney,38 and the synthesized NO itself is known to inhibit reabsorption of Na + along the nephron by reducing the respiratory rate of mitochondria8, 39, 40, 41 therefore, NO inhibits oxygen consumption. Three lines of evidence support our observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; and (3) Can the vascular and/or tubular architecture influence the observations? All NOS isoforms are expressed in the kidney,38 and the synthesized NO itself is known to inhibit reabsorption of Na + along the nephron by reducing the respiratory rate of mitochondria8, 39, 40, 41 therefore, NO inhibits oxygen consumption. Three lines of evidence support our observations.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of renal NOS activity is located in the medulla 7. On the other hand, NOS inhibition also increases renal oxygen consumption 8. Oxygen consumption efficiency is decreased in diabetic rats because of disturbed NO metabolism 9.…”
Section: Introductionmentioning
confidence: 99%
“…Another explana tion may be diminished renal nitric oxide (NO) genera tion because of endothelial damage and downregulation of endothelial NO synthase (eNOS/NOS-3). NO is a major regulator of microvascular oxygen supply and renal VO 2 [37]. Th rough vasodilation, NO increases renal blood fl ow and hence DO 2 .…”
Section: Renal Oxygenation In Clinical Ischemic Acute Kidney Injurymentioning
confidence: 99%
“…NO is inactivated by reaction with superoxide (O 2 Ϫ ) to produce peroxynitrite and increased production of superoxide has been demonstrated in SHR (13,19 -21). Manipulations that reduce superoxide production have also been shown to lower BP in these animals (19 -21).NO also modulates oxygen consumption in the whole animal and in isolated tissues, such as heart and kidney, with an inverse relationship between NO production and oxygen consumption (22)(23)(24). We have previously shown that NO production by the eNOS isoenzyme in the kidney is responsible for regulation of renal oxygen consumption (25).…”
mentioning
confidence: 99%
“…NO also modulates oxygen consumption in the whole animal and in isolated tissues, such as heart and kidney, with an inverse relationship between NO production and oxygen consumption (22)(23)(24). We have previously shown that NO production by the eNOS isoenzyme in the kidney is responsible for regulation of renal oxygen consumption (25).…”
mentioning
confidence: 99%